Konsep Etika Bisnis Islami dalam Kitab Sahih Bukhari dan Muslim - Andi Zulfikar Darussalam; A. Darussalam Tajang; A. Syathir Sofyan; Trimulato Trimulato (ITB AAS INDONESIA Surakarta, 2020)
This article verifies that hadith of Prophet Muhammad SAW. do not limit someone’s wealth amount (results) from a business activity, but limit how method (process) to acquire (result) of a business activity. It indicates that in business activity, hadis of Prophet Muhammad SAW. put more emphasis in importance of process (business ethics) compared to result, in order that there is none who would do evil deed or there is none who would suffers evil deed. This article shows that process of a business activity shall be based on business ethics. Business ethics are gathered from guideline from the Prophet Muhammad SAW. emphasized on two important things; firstly, conducting business activity with reasonable business behavior, secondly, avoiding disgraced business behavior. The business ethics have been practiced by Prophet Muhammad SAW. in conducting business activities before his appointment as Prophet. The main source of this study is texts (the Prophet’s utterance) that contained in (hadis books) Sahih al-Bukhari and Sahih Muslim. Beside of that, in order to make more deeper comprehension on those texts, supporting sources are used such as syarah al-hadith book and fiqh books. In order to read those texts are taken thematically (maudu’iy) and also to be enriched by theories and methodologies from other disciplines such as history.